Landscape, photography and affective maps: a dialogue between cultural geography and environmental psychology - Silva, Silvia Heleny Gomes da; Bomfim, Zulmira Áurea Cruz; Costa, Otávio José Lemos (Geosaberes; Vol 10 No 21 (2019): May - AugustDO - 10.26895/geosaberes.v10i21.696, 2019)
The article discusses the apprehension of reality from the category of landscape analysis, from the perspectives of cultural geography and environmental psychology. To do so, the Itaperi campus, at the State University of Ceará (UECE), was taken as study, with the objective of knowing how affective relationships are woven between students and the university. By showing how the apprehension of the landscape causes feelings in individuals and enables multiple ways of expressing their experience about places. The methodology adopted was that of the Affective Maps Generator Instrument (IGMA). The study reveals the feelings that permeate the daily experience of students with the university, through the images of belonging, pleasantness, insecurity and destruction elucidated by affective maps.